High content analysis: A sensitive tool to detect and quantify the cytotoxic, synergistic and antagonistic effects of chemical contaminants in foods. Issue 3 (18th March 2015) - Clarke, R.; Connolly, L.; Frizzell, C.; Elliott, C.T.
Highlights High content analysis (HCA) is a useful tool to determine cytotoxicity of complex mixtures. Conventional endpoints MTT and NR were compared to HCA endpoints. Tertiary mycotoxin mixture (OTA/FB1/AFB1) revealed more cytotoxicity using HCA endpoints over conventional endpoints. Binary combination (OTA/FB1) revealed synergistic interactions using HCA previously undetected by conventional endpoints.